Pengembangan Bahan Ajar Mata Kuliah Statistik pada Program Studi Pascasarjana (S-2) Teknologi Pendidikan - Buyung Buyung (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study began with learning problems related to the lack of statistics teaching materials that suit students' needs and there are no resources that suit the statistics syllabus. Learning resources are taken from several books whose material is still separated from each other, the material is difficult to understand because the language used is not applied and there are no examples for application in research that will be used by students in their final assignment. The aim of this research is to develop teaching materials for statistics courses that suit student needs, test the feasibility of the statistics teaching materials being developed, and see the effectiveness of using statistics teaching materials in the implementation of learning. The research method used is research and development (R&D), namely the Dick and Carey model. The research subjects were material experts, media experts, design experts, and students of the first semester of the 2022/2023 academic year 2022/2023 master's study program (classes A, B, and C). Instrument Data collection uses observation sheets, interviews and questionnaires. The data analysis used is quantitative and qualitative analysis. The result of this research is that in the implementation of learning there are no teaching materials that are in accordance with the syllabus so that taking from several sources, the model used in developing the product is the Dick and Carey model with the results of the feasibility test through formative evaluation on statistical teaching materials declared suitable for use and in implementation learning is declared effective.